IMPLEMENTING JIGSAW-TYPE COOPERATIVE MODEL ON THE STUDENTS’ THEMATIC LEARNING OUTCOMES AT GRADE V SD NEGERI 003 RAMBAH - Robina Simanjuntak (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to find out that the implementation of Jigsaw-type cooperative learning to improve students’ thematic learning outcomes at grade V SD Negeri 003 Rambah. This research was classroom action research. The technique of data analysis was conducted by collecting several instruments such as students’ and researchers’ activity sheets and question sheets. The results of this study showed that at the first meeting in cycle I, 20 students (64.51%) reached KKM with the class average score of 72.25. Then, at the second meeting in cycle I, 21 students (67.41%) reached KKM with a class average score of 74.83. Moreover, at the first meeting in cycle II, it was found that 26 of 31 students (83.87%) reached the KKM with an increased in the average score to 84.03. Then, at the second meeting, the students’ learning outcomes obtained a very satisfied result, in which 28 of 31 students (90.32%) reached KKM with an average score of 86.12. The conclusion of this study was that implementing Jigsaw-type cooperative model in learning thematic improved the students’ learning outcomes at the fifth grade SD Negeri 003 Rambah.